Incidence of Invasive Pneumococcal Disease Before and During an Era of Use of Three Different Pneumococcal Conjugate Vaccines in Quebec. (4th October 2017) - De Wals, Philippe; Lefebvre, Brigitte; Deceunicnk, Geneviève; Longtin, Jean
Abstract: Background: In Quebec, 7-valent (PCV7), 10-valent (PCV10) and 13-valent (PCV13) pneumococcal conjugate vaccines were successively used for children immunization according to a 2 + 1 doses schedule. Objective: To assess the impact of this program on the epidemiology of invasive pneumococcal disease (IPD). Methods: Notification (2000–2016) and laboratory surveillance (2005–2016) data were analyzed and the immunization status of IPD cases in 2011–2015 was checked. Results: In children <5 years, IPD rate decreased from 69/100, 000 in 2003 to 12/100, 000 in 2016 (83% reduction). Following PCV7 introduction in 2004, there was a rapid decline in incidence of homologous serotypes. 7F cases and 19A decreased following PCV10 introduction in 2009 and PCV13 in 2011, whereas decrease in serotype 3 IPD was minimal. Non-vaccine types IPD increased and represented 79% of cases in 2016. The same pattern was seen in adults but replacement was complete and there was no decrease in overall IPD rate. In those 65 years and over, PCV13 serotypes represented 28% of cases in 2016, and 62% were covered by the 23-valent polysaccharide vaccine. Out of 7 IPD cases caused by serotype 3 in children vaccinated with PCV13, 5 occurred more than one year following the booster dose, which suggests short-term protection. Out of 27 breakthrough 19A cases, 17 occurred between 8 and 14 months of age in children who had received the 2 primary PCV13 doses but not the toddler booster dose, which suggests a window of susceptibility in a 2 + 1 schedule. Conclusion: Hopefully, 19A incidence in children will continue to decrease and herd protection would eventually close the window of susceptibility. Serotype 3 is fortunately not frequent in children but a hard nut to crack. In elderly adults, PCV13 serotype coverage is diminishing year after year but a majority of cases remains potentially covered by the 23-valent polysaccharide vaccine. Disclosures: P. De Wals, GSK: Investigator and Scientific Advisor, Research grant and Travel expenses; Pfizer: Grant Investigator and Scientific Advisor, Research grant and Travel expenses; SanofiPasteur: Grant Investigator, Research grant and Travel expenses